Ontogenetic trajectories of key morphofunctional cranial traits in South American subterranean ctenomyid rodents - Verzi, Diego Hector (2010)
Ontogenetic allometries of craniomandibular and dental features linked to digging were analyzed in 5 species of the South American subterranean rodent Ctenomys (tuco-tucos). With the exception of upper incisor procumbency, variables showed high correlation with overall skull size. In particular, craniomandibular variables related to the production of bite forces at the incisors showed near-geometric similarity during postnatal growth and interspecific changes in early developmental stages resulting in different starting forms (lateral transposition). Such an interspecific pattern of change is similar to one previously reported to occur among living and extinct ctenomyid genera. These results suggest more evolutionary flexibility for changes in early ontogenetic stages and allow rejection of the hypothesis that interspecific shape differences in the skull of Ctenomys would be associated with differences in size alone. © 2010 American Society of Mammalogists.